Development of a novel mobile flexible hysteroscopy system for outpatient procedures without general anaesthesia - Wessels, Edmund (Department of Human Biology, 2025)
Introduction: Hysteroscopy is regarded as the gold standard for evaluating and treating abnormal uterine conditions and while typically performed in the operating room with general anaesthesia, office procedures without general anaesthesia has been proven to be safe and efficient. However, shortcomings with existing hysteroscopy systems, such as patient discomfort and equipment cost, impede the adoption and success of office hysteroscopy. This research project aimed to develop a new hysteroscopy system that was more accessible to gynaecologists by reducing cost, eliminating equipment requirements, and improving the patient experience. This increases the rate of office hysteroscopy and, as a result, improves patient access to the procedure. Materials & Methods: By reviewing the current hysteroscopy landscape, need criteria were determined and translated into design requirements to guide the design and development of the new hysteroscopy system. The design process followed an iterative prototyping approach where prototypes were built on the previous version until a system that met all the design requirements was developed. The prototype system then underwent verification testing to establish the design specifications to compare against the design requirements and, if successful, proceed to validation testing through a comparative usability trial. The trial protocol was developed according to the IEC 62366-1:2015 standard using an ISO 14971:2019 risk analysis as input. The trial involved 10 gynaecologists performing simulated procedures with the prototype and a standard system, thereafter, providing feedback through a System Usability Scale, a post-session questionnaire, and a procedure review form. Results & Discussion: The outcome of the design process was a mobile flexible hysteroscopy system with a single-use sheath with a channel for distention media. The prototype was all-in-one with a built-in camera, light source, and battery power source, and it could be operated single-handedly. It was verified to have a 260mm working length, 4.2mm diameter scope with a 236° bending range, 79 minutes of continuous usage, and the disposable sheath could isolate the system while fully submerged and supply saline solution at over 200 mmHg pressure. The trial results showed the prototype system to have higher usability than the standard, scoring 86 and 67, respectively. Furthermore, less experienced gynaecologists scored the prototype system much higher than the standard, indicating it was easier to use. This was further shown in the post-session questionnaire, where a Mann-Whitney U test determined the significance between ratings of the two systems, and the prototype system was found to be significantly easier to clean, set up, and use. Finally, the procedure review form confirmed all participants could perform a hysteroscopy procedure with the prototype system without using tools such as a speculum or tenaculum. The prototype system was therefore validated as a functional hysteroscopy system that successfully incorporated features to address the identified shortcomings of existing hysteroscopy systems. Conclusion: The research project, therefore, successfully achieved its aim, having developed the prototype hysteroscopy system that could increase the adoption of office hysteroscopy procedures. This is possible through the system requiring no additional equipment and sterilisation facilities while offering an improved user and patient experience through the user-friendly design, minimal diameter flexible scope, and not requiring tools during procedures. Future work could be aimed at refining the hysteroscopy system and preparing it for the first human testing to demonstrate clinical safety and efficacy.